2017
DOI: 10.1007/s00246-017-1596-7
|View full text |Cite
|
Sign up to set email alerts
|

Low Iron Stores in Otherwise Healthy Children Affect Electrocardiographic Markers of Important Cardiac Events

Abstract: Both an excess of iron and iron deficiency (ID) may lead to significant cardiac problems. Parameters that represent ventricular repolarization heterogeneity, like QT dispersion (QTd), corrected QT dispersion (QTcd), the interval between the peak and the end of the T wave (Tp-e), and Tp-e dispersion, have not been evaluated in otherwise healthy children with low iron levels before. Here we assessed the effects of low iron storage on P wave dispersion (PWd), QTd, Tp-e intervals, and Tp-e dispersion in otherwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…P wave dispersion was not measured if fewer than nine leads were eligible for analysis. 12 The QT interval was measured from the beginning of the QRS complex to the end of the T wave and corrected for heart rate using the Bazett formula (QTc = QT/ p R − R interval). 13 The QT dispersion was calculated for at least 8 of the 12 leads and usually included leads I, II, and V5.…”
Section: Electrocardiography and Echocardiographymentioning
confidence: 99%
See 2 more Smart Citations
“…P wave dispersion was not measured if fewer than nine leads were eligible for analysis. 12 The QT interval was measured from the beginning of the QRS complex to the end of the T wave and corrected for heart rate using the Bazett formula (QTc = QT/ p R − R interval). 13 The QT dispersion was calculated for at least 8 of the 12 leads and usually included leads I, II, and V5.…”
Section: Electrocardiography and Echocardiographymentioning
confidence: 99%
“…The differences between the maximum and minimum QT and QTc intervals were defined as the QT and QTc dispersions, respectively. 12 The T peak to end interval was defined as the interval from the peak of T wave to the end of T wave. We defined T peak to end as the intersection point of the tangent to the downward slope of the T wave with the isoelectric line.…”
Section: Electrocardiography and Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Tp-e interval is a noninvasive scanning method for arrhythmogenesis and Tp-e interval can be approved as a crucial index in showing sudden cardiac death risk. There are studies in literature displaying that Tp-e/QT rate independent from Tp-e is a more reliable and stable index 34,35 . In a study that Tp-e/QT rate and its use were assessed, measurements were carried out in 60 healthy volunteers and it was shown that Tp-e interval decreased in a linear way with increase in heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…HR increases in case of low hemoglobin levels in the blood. The increase in HR causes tachycardia and can trigger AVNRT via atrial ectopic beats (28) . Yo et al showed that aging affects the LF/HF ratio in healthy and hypertensive subjects (29) .…”
Section: Discussionmentioning
confidence: 99%